Rest‐activity rhythm phenotypes in adults with epilepsy and intellectual disability - Nandani Adhyapak; Grace E. Cardenas; Mark A. Abboud; Vaishnav Krishnan (Epilepsia Open)
Abstract Objective Rest‐activity rhythms (RARs) are perturbed in many forms of neuropsychiatric illness. In this study, we applied wrist actigraphy to describe RAR perturbations in intellectually disabled adults with epilepsy (“E + ID”), using a cross‐sectional case–control design. We examined whether RAR phenotypes correlated with epilepsy severity, deficits in adaptive function, and/or comorbid psychopathology. Methods Caregivers of E + ID subjects provided informed consent during routine ambulatory clinic visits and were asked to complete standardized surveys of overall epilepsy severity (GASE, Global Assessment of Severity of Epilepsy), adaptive function (ABAS‐3, Adaptive Behavior Assessment System‐3) and psychopathology (ABCL, Adult Behavior Checklist). Caregivers were also asked to ensure that subjects wore an Actiwatch‐2 device continuously for at least ten days. From actograms, we calculated RAR amplitude, acrophase, robustness, intradaily variability (IV), interdaily stability (IS), and estimates of sleep quantity and timing. We compared these RAR metrics against those from (i) a previously published cohort of adults with epilepsy without ID (E–ID), and (ii) a historical control cohort of age‐ and sex‐matched intellectually able subjects from the Study of Latinos (SOL). Results 46 E + ID subjects (median age 26, 47% female) provided a median recording duration of 11 days. Surveys reflected low to extremely low levels of adaptive function and low/subclinical levels of psychopathology. Compared with E‐ID and SOL cohorts, E + ID subjects displayed significantly lower measures of RAR amplitude, robustness, and IS, with significantly higher IV and total daily sleep. K‐means clustering of E + ID subjects recognized a cluster with pronounced hypoactivity, hypersomnia, and elevated rhythm fragmentation (cluster A), an intermediate group with metrics similar to E‐ID, and cluster “C” subjects that featured hyper‐robust and high amplitude RARs. All three clusters were similar in age, body mass index, antiseizure medication (ASM) polytherapy, ABAS3, and ABCL scores. Significance Adults with epilepsy and intellectual disability display a wide spectrum of RAR phenotypes that do not neatly correlate with measures of adaptive function or epilepsy severity. Prospective studies are necessary to determine whether continuous actigraphic monitoring can sensitively capture changes in chronobiological health that may arise with disease progression, ASM side effects, or other acute health deteriorations. Plain Language Summary Rest‐activity rhythms (RARs) can be measured using continuously worn wrist activity monitors. We show that compared to controls, adults with epilepsy and intellectual disability (E + ID) display RARs that are more fragmented, weaker in amplitude, and unstable across days. Within our E + ID cohort, we observed a wide spectrum of RAR phenotypes that we clustered into three subtypes, which were similar in overall average measures of adaptive functioning and psychiatric symptoms.